دراسة تحليلية لعوامل الاخفاق والتفوق لبطل الوثب العالي مجد الدين غزال - المحيسني, عماد (Latakia University Journal -Medical Sciences Series, 2018)
تعد عوامل الاخفاق والتفوق من أهم العوامل التي تضمن للبطل الرياضي التفوق على غيره, وذلك من خلال تلافي عوامل الاخفاق والعمل على تعزيز عوامل التفوق الرياضي وتطويرها, لذا كان التعرف عن كثب للسيرة الذاتية للبطل (محد الدين غزال) وكذلك التعرف على أهم عوامل الاخفاق والتفوق للبطل هو الهدف الرئيسي لهذه الدراسة, وذلك باستخدام المنهج الوصفي بأسلوب دراسة الحالة للبطل (مجد الدين غزال), وتوصلت الدراسة إلى أن أهم عوامل التفوق للبطل الرياضي هي الأسرة رياضية, التي تشكل القيمة المثالية لنمو الموهبة الرياضية, والمقومات الجسدية المثالية التي توافرت في البطل مجد الدين غزال, فضلاً عن السمات النفسية التي تحلى بها (رغبة عالية بالإنجاز, حب شديد للرياضة, اجتماعي, الثقة بالنفس, قيادي, التحدي, الطموح, والالتزام), وتمازج خبرة التدريب الدولية مع الخبرة الوطنية تشكل قاعدة تكوّن للبطل الرياضي, ورسم صورة المستقبل الواضحة للموهوب الرياضي لتدفعه لتحقيق حلمه بثقة وثبات, فيما كانت أهم عوامل الاخفاق للبطل الرياضي هي عدم التنظيم الدقيق بين العمل التدريبي والعمل والدراسة, وعدم وجود مراكز طبية وأطباء مختصين بالإصابات الرياضية على سوية عالية, وغياب الثقافة الرياضية عند البعض من القيادات الرياضية ذات العلاقة باللعبة تشكل صعوبات تعرقل مسيرة البطل الرياضي. The factors of failure and superiority are among the most important factors that ensure the athlete's superiority, by avoiding the factors of failure and work to strengthen the factors of sports excellence and development, so was to identify closely the biography of the champion (Majd al-Din Ghazal) as well as identify the most important factors of failure and superiority of the hero is The main objective of this study. By using the descriptive approach in the case study method of the champion (Majd al-Din Ghazal). The study concluded that the most important factors of excellence for the athlete are the family, which is the ideal value for the growth of sports talent. As well as the psychological qualities he has shown (high desire for achievement, great love for sport, social, self-confidence, leadership, challenge, ambition and commitment), the combination of international training experience with national experience form the basis of the athlete's hero, and drawing a clear picture of the future of the sport talented person which will motivate him to achieve his goals with stability and confidence while the main failure factors of the athlete are the lack of organising in the training courses and the work and the studying time and the lack of the availability of the medical centers and professional medical specialists for sports injuries and the lack of the sports cultural knowledge of some of the sports leaders that causes a lot of difficulties in the bath of the sports champion.